2017
DOI: 10.1007/s12640-017-9788-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Withdrawal Increases Brain-Derived Neurotrophic Factor Precursor

Abstract: Morphine has been shown to increase the expression of brain-derived neurotrophic factor (BDNF) in the brain. However, little is known about the effect of morphine withdrawal on BDNF and its precursor protein, or proBDNF, which induces neuronal apoptosis. In this work, we examined whether BDNF and proBDNF levels change in rats chronically injected with escalating doses of morphine and those who undergo spontaneous withdrawal for 60 hr. We observed, in the frontal cortex and striatum, that the ratio of BDNF to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…In agreement with our results, it has been described that formation of aversive memories associated with conditioned morphine withdrawal requires BDNF signaling pathway in the rat amygdala . Moreover, morphine treatment and morphine withdrawal increased both pro‐BDNF and BDNF levels in frontal cortex . However, the molecular mechanism by which BDNF elicits the formation of aversive memories associated with conditioned morphine withdrawal remains poorly understood.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with our results, it has been described that formation of aversive memories associated with conditioned morphine withdrawal requires BDNF signaling pathway in the rat amygdala . Moreover, morphine treatment and morphine withdrawal increased both pro‐BDNF and BDNF levels in frontal cortex . However, the molecular mechanism by which BDNF elicits the formation of aversive memories associated with conditioned morphine withdrawal remains poorly understood.…”
Section: Discussionsupporting
confidence: 90%
“…47 Moreover, morphine treatment and morphine withdrawal increased both pro-BDNF and BDNF levels in frontal cortex. 48 However, the molecular mechanism by which BDNF elicits the formation of aversive memories associated with conditioned morphine withdrawal remains poorly understood. In our present study, we found that BDNF expression significantly increased after FIGURE 5 Western blotting analysis of pERK, pCREB, pro-brain-derived neurotrophic factor (BDNF), and BDNF in dentate gyrus (DG) after conditioned place aversion (CPA) extinction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, morphine exposures in vivo appear to increase the extracellular protease tissue plasminogen activator, thus increasing cleavage of proBDNF to mBDNF. Withdrawal from morphine had the opposite effect [ 69 ]. Intracellular conversion of proBDNF to mBDNF in neurons is reduced by the HIV surface envelope protein gp120, which reduces levels of the intracellular protease furin [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exogenous tPA administration increases hippocampal BDNF levels and the conversion of pro‐BDNF to BDNF by plasmin is essential for LTP late‐phases . In addition, a defective tPA/plasmin/PAI‐1‐mediated BDNF maturation has been claimed to be involved in the manifestation of some brain pathologies, such as substance abuse and addiction, depression, and stress …”
Section: Plasminogen Activation System and The Regulation Of Bdnf Matmentioning
confidence: 99%